Molecular mechanism of protein-retinal coupling in bacteriorhodopsin. - Delaney, J K (1995)
Bacteriorhodopsin is a membrane protein that functions as a light-driven proton pump. Each cycle of proton transport is initiated by the light-induced isomerization of retinal from the all-trans to 13-cis configuration and is completed by the protein-driven reisomerization of retinal to the all-trans configuration. Previous studies have shown that replacement of Leu-93, a residue in close proximity to the 13-methyl group of retinal, by alanine, resulted in a 250-fold increase in the time required to complete each photocycle. Here, we show that the kinetic defect in the photocycle of the Leu-93-->Ala mutant occurs at a stage after the completion of proton transport and can be overcome in the presence of strong background illumination. Time-resolved retinal-extraction experiments demonstrate the continued presence of a 13-cis intermediate in the photocycle of the Leu-93-->Ala mutant well after the completion of proton release and uptake. These results indicate that retinal reisomerization is kinetically the rate-limiting step in the photocycle of this mutant and that the slow thermal reisomerization can be bypassed by the absorption of a second photon. The effects observed for the Leu-93-->Ala mutant are not observed upon replacement of any other residue in van der Waals contact with retinal or upon replacement of Leu-93 by valine. We conclude that the contact between Leu-93 and the 13-methyl group of retinal plays a key role in controlling the rate of protein conformational changes associated with retinal reisomerization and return of the protein to the initial state.